Perceived and Physical Quality of Drinking Water in Pavlodar and AkmolaRural Regions of Kazakhstan - Beisenova, R.; Tussupova, K.; Tazitdinova, R.; Tulegenova, S.; Rakhymzhan, Zh.; Orkeyeva, A.; Alkhanova, Ye.; Myrzagaliyeva, A.; Nugmanov, A.; Zhupysheva, A. (Sustainability, 2024)
Water quality in rural areas of developing countries is a notable problem. In this article, drinking water quality from eleven villages in the Pavlodar and the Akmola region of Kazakhstan was analyzed. Questionnaires of village respondents and chemical components of drinking water were analyzed to identify the quality of drinking water. In each of the villages, the chemical content varied depending on the source of drinking water. In the rural Pavlodar region, we observed that some cations and anions exceed the MPC. Respondents’ perceptions of water quality are associated with water sources and physical components. For example, respondents’ satisfaction by inside tap of central water systems’ water was high, the answers of those whose water source was private wells showed more mixed satisfaction levels. The drinking water physical quality indicators are closely related to water mineralization and general hardness. The total microbial count of drinking water has a significant relationship with respondents’ complaints about unpleasant taste, odor, and salinity. The relationship between perceived and physical water quality is a critical aspect of water resource management. By bridging the gap between scientific assessments and public perceptions, we can enhance public health, build trust in water management systems, and promote sustainability of water use.
Keywords: chemicals; quality; rural; source; drinking water; manganese; cations; anions; perseverance